2010
DOI: 10.1186/1471-2431-10-46
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of adenovirus causing respiratory tract infection in pediatric patients at the University of Malaya Medical Center

Abstract: BackgroundThere are at least 51 adenovirus serotypes (AdV) known to cause human infections. The prevalence of the different human AdV (HAdV) serotypes varies among different regions. Presently, there are no reports of the prevalent HAdV types found in Malaysia. The present study was undertaken to identify the HAdV types associated primarily with respiratory tract infections (RTI) of young children in Malaysia.MethodsArchived HAdV isolates from pediatric patients with RTI seen at the University of Malaya Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 26 publications
12
40
1
Order By: Relevance
“…Our data underscore the important role of HAdV in adult ARTIs in China. The 0.8% detection rate of HAdV in this study is lower than the 2.0 to 9.14% reported in several previously published studies [12,22,23]. This disparity cannot be attributed to the detection method used, as our PCR experiments which target a different hexon gene fragment and a different gene (E1A) are consistent with our PCR screening results.…”
Section: Discussionsupporting
confidence: 45%
“…Our data underscore the important role of HAdV in adult ARTIs in China. The 0.8% detection rate of HAdV in this study is lower than the 2.0 to 9.14% reported in several previously published studies [12,22,23]. This disparity cannot be attributed to the detection method used, as our PCR experiments which target a different hexon gene fragment and a different gene (E1A) are consistent with our PCR screening results.…”
Section: Discussionsupporting
confidence: 45%
“…Another report observed that 23% of the pathogens causing acute respiratory disease in 100 Mexican children were HAdVs, with all of the isolates identified as species C exclusively (32), including HAdV-C6. This was also observed in a recent survey of Malaysian HAdV respiratory tract infections, which noted that species C were the most commonly isolated HAdV among pediatric patients in a 7-year period (1).…”
supporting
confidence: 49%
“…A similar study in which high HAdV infections (47.6%) were shown at the age group ≤ 1 to ≥3 years compared to age group 3-≤ 6 years and 6-≤ 15 years at 28.1%, 11%, respectively [35]. The study finding is also, comparable to other studies of HAdV infection in other part of the world indicating that children under the age of 3 years were most susceptible to HAdV infection [36][37][38]. In previous experiments for the detection of HAdV in RTI, we observed that Children at age between 6 to 15 years usually have a lower rate of infection.…”
Section: Molecular Diagnosis Of Human Adenovirus In Children With Uppsupporting
confidence: 80%